Mensuração de hormônios andrógenos, estrógeno, fosfatase ácida prostática (PAP) e antígeno prostático específico (PSA) em cães adultos com próstata normal e hiperplásica - Moura, Veridiana Maria Brianezi Dignani de; di Santis, Giovana Wingeter; Amorim, Renée Laufer [UNESP]; Balieiro, Júlio César; Bandarra, Enio Pedone (My University, 2006)
Prostatic diseases have been a common problem in middle age and older intact male dogs. Among these, benign prostatic hyperplasia (BHP) is the most frequent, age-related and hormonal-dependent condition of human and canine prostate. Blood samples were collected from 37 male intact dogs, tree years old dogs or more to determine androgens, estrogen, prostatic acid phosphatase (PAP) and prostatic specific antigen (PSA) according to histopathological aspects. Low levels of estrogen and high levels of prostatic specific antigen (PSA) were founded in dogs with BHP, respectively. Seric and urinary PAP levels were high in dogs with hyperplasia.
Androgens, estrogen, prostatic acid phosphatase (PAP) and prostatic specific antigen (PSA) measure in adult male dogs with normal and hyperplasic prostate
Keywords: Canine benign prostatic hyperplasia; Dihydrotestosterone; Dog; Estrogen; Immunohistochemistry; Prostate; Testosterone; Canis familiaris